2 in 1 IV-STEM french fries machine - Khamis, Ahmad Hakim; Suwandi, Siti Rafhanah; Md Noh, Siti Nurfarisya; Mohd Hisammuddin, Emier Hedzriq; Sulaiman, Nur Afifah; Tukiman, Norbaiti (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Knife and potato peeler are typically used by people to peel and cut the potatoes. People still use this manual method because it gives no cost and no use of electricity. This manual method consumes time and energy of human manpower that can lead to the risk of injuries. Therefore, this project aims to overcome the issue rise with analysis, design and fabrication 2 in 1 French fries machine. This machine consists of two processes which are peeler and cutter. Next, 2 in 1 French fries machine is a semi-automatic machine that is able to peel two kilogram potatoes per process and cut the potatoes to the French fries’ size and shape. The peeler machine uses the abrasive technique to peel the potato skin. The potato skin peels off when the disc rotates and it collides with the cylinder drum wall. The cutter machine uses the electric linear actuator to push the potato to the cutting blade. The fabrication of this machine mostly uses the stainless steel material. Other than that, simple machine material like motor and shaft used to rotate the disc on the peeler machine. Last but not least, this product has the potential to grow and be commercialized as it gives an alternative way to the user during the peeling and cutting process.